2020
DOI: 10.1016/j.transci.2020.102922
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 serology and virology trends in donors and recipients of convalescent plasma

Abstract: SARS-CoV-2 has infected millions worldwide. The virus is novel, and currently there is no approved treatment. Convalescent plasma may offer a treatment option. We evaluated trends of IgM/IgG antibodies/plasma viral load in donors and recipients of convalescent plasma. 114/139 (82 %) donors had positive IgG antibodies. 46/114 donors tested positive a second time by NP swab. Among those retested, the median IgG declined (p < 0.01) between tests. 25/139 donors with confirmed SARS-CoV-2 were negative for IgG antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…This implies that the time from disease onset to antibody evaluation has an impact on the detected titers of anti-SARS-CoV-2 antibodies. This is consistent with previous studies showing that antibody levels decrease over time [9,16,19,27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This implies that the time from disease onset to antibody evaluation has an impact on the detected titers of anti-SARS-CoV-2 antibodies. This is consistent with previous studies showing that antibody levels decrease over time [9,16,19,27].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we did not find any association between antibody production and blood type. This is also consistent with previous reports in the field [27]. Several studies have shown that blood type is not a prognostic factor for dismal outcomes among patients with symptomatic Covid-19 disease [32].…”
Section: Discussionsupporting
confidence: 93%
“…The latter would be consistent with the variable antibody responses now determined for the spectrum of pediatric disease [44]. For EIA-based antibody studies otherwise, we have learned so far that the type and severity of disease and age may have bearing on the quality and quantity of antibody responses [34,[45][46][47][48]. Gender may also possibly affect antibody responses or other relevant immune responses [34,49].…”
Section: Provisional Acceptance Of What Constitutes Immunitysupporting
confidence: 64%
“…Laboratories that only report a positive or negative value do not detect this large variability. Moreover, only about 50% of RNA positive outpatients had IgG levels >6.5 AU/mL, sufficient to provide estimated antibody titers of >1:320 as per FDA guidance, and only about one-third had plasma IgG levels >20 AU/mL, sufficient to provide estimated antibody titers >1:1000 [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Antibody testing has been reported to be useful for documenting exposure and potential immunity, as well as for case finding in family clusters and exposed individuals [9][10][11][12][13][14][15]. Moreover, treatment of hospitalized COVID-19 patients with convalescent plasma rich in antibodies may be useful in treating the disease [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%